2015
DOI: 10.1002/asna.201412196
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the photoelectric light curve and the orbital period variations of the binary system UU Andromedae

Abstract: In this work, the analysis of the photoelectric light curve (LC) in the broad‐band filter (400–700 nm) for the UU And system was carried out using the PHOEBE program (vers. 0.31a). The absolute dimensions of the system are determined and its evolution is discussed. Moreover, the period changes of the system are studied using updated O – C data, which shows a cyclic change with a period of Pmod = 18 yr. This was attributed to a magnetic activity cycle operating in this system. In addition to the cyclic change, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Up to the present, O-C based orbital period analysis studies have only been presented by Qian (2001) and Manzoori et al (2015). Qian (2001) made a period analysis of UU And using 150 visual and photographic primary minimum times.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Up to the present, O-C based orbital period analysis studies have only been presented by Qian (2001) and Manzoori et al (2015). Qian (2001) made a period analysis of UU And using 150 visual and photographic primary minimum times.…”
Section: Introductionmentioning
confidence: 99%
“…Secular mass and angular momentum loss were suggested as possible mechanisms of the orbital period decrease. Manzoori et al (2015) re-examined the O-C changes of UU And with 183 minimum times observed from 1911 to 2008. Out of 183, 36 were photoelectric (Pe) minimum times observed under the WASP survey (Pollacco et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An O-C diagram of UU And in the time interval 1973-1986 was published in [27], who pointed out two distinct period jumps, the first was roughly in 1976 and the second in 1983. The study of period variations of the system was made in [35], a period decrease of the order of dP/dt = 4.76 • 10 −7 d/yr was reported in [26].…”
mentioning
confidence: 99%